2006
DOI: 10.1042/cs20060104
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase activity does not contribute to the maintenance of peripheral vascular tone in patients with heart failure

Abstract: Enhanced iNOS (inducible nitric oxide synthase) activity may contribute to vascular dysfunction in patients with heart failure. In the present study, we aimed to determine whether iNOS activity contributes to the maintenance of vascular tone in patients with symptomatic heart failure with the use of the highly selective iNOS inhibitor 1400W {N-[3-(aminomethyl)benzyl] acetamidine}. Bilateral forearm blood flow was measured using venous occlusion plethysmography in 12 patients with New York Heart Association cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…Moreover, our loss-of-function studies identify many genetic targets for NOS2 in GSCs (including the cell cycle inhibitor protein CDA1), providing novel mechanistic information distinct from previous studies using exogenous NO donors. Finally, NOS2 inhibition may represent an anti-glioma treatment option with an acceptably low toxicity profile, as demonstrated by the negligible toxicity of NOS2 inhibitor administration to humans (Brindicci et al, 2009; Dover et al, 2006; Singh et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our loss-of-function studies identify many genetic targets for NOS2 in GSCs (including the cell cycle inhibitor protein CDA1), providing novel mechanistic information distinct from previous studies using exogenous NO donors. Finally, NOS2 inhibition may represent an anti-glioma treatment option with an acceptably low toxicity profile, as demonstrated by the negligible toxicity of NOS2 inhibitor administration to humans (Brindicci et al, 2009; Dover et al, 2006; Singh et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the effects of 1400 W on foetal development are not known, even though this iNOS inhibitor has been used in a number or animal studies and in a few studies in humans [38, 39]. Moreover, while there is evidence supporting a pathogenic role for increased oxidative stress in clinical pre-eclampsia [8, 40], most clinical trials do not support antioxidant therapy for prevention or therapy of pre-eclampsia [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated levels of ADMA have been proposed as a predictor of adverse cardiovascular outcomes in patients with heart failure [66]. In contrast, several clinical studies have demonstrated that patients with heart failure exhibit an increased responsiveness to inhibitors of NO synthesis and elevated plasma levels of stable NO breakdown products [67-70], suggesting that NO synthesis is increased rather than decreased. …”
Section: L-arginine – No Pathway In Chronic Heart Failurementioning
confidence: 99%